Study on indiscriminate use of antibiotics in poultry feed and residues in broilers of Mymensingh city in Bangladesh - Khan, MI; Ferdous, J; Ferdous, MRA; Islam, MS; Rafiq, K; Rima, UK (Progressive Agriculture, 2019)
Abstract Knowledge, attitude and practice of broiler sellers about the indiscriminate use of antibiotic in poultry feed and antibiotic residue status of broiler in the live bird market of Mymensingh city was investigated. Twenty live poultry selling shops were randomly interviewed and six broilers from each market (5x6= 30) were randomly selected for detection of residual antibiotics in the liver and breast muscle. All the broiler meat sellers were male and the number of participants appeared higher in 21-30 year age group. The proportion of different age groups found to vary significantly (P<0.01). Among them, 10% sellers were illiterate, 60% sellers merely cross primary education, 25% sellers had secondary education and 5% sellers reached level of higher education. All sellers were familiar with antibiotics and vitamins. About 57.5% and 22.5% of the broiler sellers had knowledge onto the use of antibiotic as growth promoter. Only 7.5% sellers understood the term antibiotic resistance and 12% had little knowledge on human health hazard following indiscriminate use of antibiotics. All broiler sellers provided commercial feed and water throughout selling period, whereas, 77.5% and 17.5% of them used mixed vitamins and antibiotics in water to prevent unwanted mortality. In terms of adding extra antibiotics in feed, 32.5% of the sellers depended on feed sellers and only 20% of them used prescription provided by the registered veterinarian. The residue of ampicillin, ciprofloxacin and enrofloxacin in liver and meat of broilers were evaluated by using thin layer chromatography (TLC). The highest percentages of antibiotic residues were detected in the birds of Kachijhuli bazar (26.67%) and lowest in Shankipara bazar (13.33%). The highest percentages of antibiotics used in poultry feed was enrofloxacin (46.67%) followed by ciprofloxacin (30.00%) and amoxicillin (23.33%). In addition, amoxicillin plus ciprofloxacin (30%) and ciprofloxacin plus enrofloxacin (43.33%) were commonly found in the liver of broilers. All the broilers had antibiotic residue in their liver and breast meat containing antibiotic residues in 20% cases. Amoxicillin, ciprofloxacin and enrofloxacin were routinely used in poultry feed and the meat sellers had little knowledge about the indiscriminate use of antibiotics in poultry sector. Therefore, community base awareness regarding the discriminate and indiscriminate use of antibiotics in poultry sector is essential, and to evaluate the effect of residual antibiotics in the broilers onto the resistance of common bacterial pathogens living in the gut & systems. Progressive Agriculture 29 (4): 345-352, 2018